1997
DOI: 10.1021/ja9709132
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Medium Ring Ethers. 5. The Synthesis of (+)-Laurencin

Abstract: The enantioselective synthesis of (+)-laurencin 1 has been achieved in 27 steps from (R)-malic acid 20.The key steps involved methylenation of the lactone 49 followed by intramolecular hydrosilation of the enol ether 14 (Scheme 11) and one carbon homologation of the diol 13 to give the key ethyl substituted cyclic ether 59 (Scheme 13). The lactone 49 was obtained by two efficient routes, namely a Claisen ring expansion (Scheme 3) followed by R-hydroxylation (Scheme 6) and a Yamaguchi lactonization (Scheme 11).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(85 citation statements)
references
References 85 publications
(155 reference statements)
2
81
0
1
Order By: Relevance
“…Our experiments showed that with borane methyl sulfide (BMS)-NaBH 4 , the chemoselective reduction of ester 3 could be achieved and gave the diol 4 in good yield, according to the literature precedents. [27][28][29][30][31] The reason for the chemoselectivity was discussed by Moriwake et al 54 The best ratio for BMS: NaBH 4 :ester 3 was 1:0.1:1. Excess BMS could lead to over-reduction and thus lower yield was obtained.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Our experiments showed that with borane methyl sulfide (BMS)-NaBH 4 , the chemoselective reduction of ester 3 could be achieved and gave the diol 4 in good yield, according to the literature precedents. [27][28][29][30][31] The reason for the chemoselectivity was discussed by Moriwake et al 54 The best ratio for BMS: NaBH 4 :ester 3 was 1:0.1:1. Excess BMS could lead to over-reduction and thus lower yield was obtained.…”
Section: Resultsmentioning
confidence: 97%
“…Aldehyde 6 was obtained from the reduction of ester 5 with DIBAL-H in excellent yield according to the literature procedure. 28,32,33 Over-reduction could be restrained by using 1.0-1.15 equivalent DIBAL-H employed and shorter reaction time (30 min). Moreover, the over-reduction product could be oxidized to aldehyde 6 with Dess-Martin reagent at rt in quantitative yield.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent Baeyer-Villiger oxidation [40] with m-CPBA, buffered with Na 2 HPO 4 , in CH 2 Cl 2 furnished the lactone 9 in 87% yield.…”
Section: [Ira C H T U N G T R E N N U N G (Cod)mentioning
confidence: 99%
“…O rearranjo de ceteno-acetais vinil-e alquenil-substituídos, preparados in situ a partir de fenil seleno-acetais ou de carbonatos, vem sendo bastante explorado na síntese de lactonas de anel mé-dio, pelo grupo de Holmes e Burton [93][94][95][96][97][98] . Em 1997, foi relatada 93 a síntese assimétrica da (+)-laurencina, um éter cíclico de 8 membros.…”
Section: Rearranjo De Claisenunclassified